Perbandingan Kebugaran Jasmani dan Indeks Massa Tubuh: Analisis Dampaknya terhadap Kesehatan - Hudain, Muh. Adnan; Fatoni, Fatoni; Fauzan, Lazuardy Akbar; Alim, Bahrul; Awal, Asri (Prodi Pendidikan Jasmani dan Olahraga, 2025)
This study aims to explore the relationship and comparison between physical fitness and Body Mass Index (BMI) in college students. A total of 50 students were randomly selected as the study sample. Physical fitness was measured using a series of standardized fitness tests, while BMI was calculated based on the formula of body weight (kg) divided by the square of height (m²). Data analysis used descriptive and inferential statistical techniques to identify patterns of relationships and differences between variables. The results showed that students with a BMI in the normal category had a significantly higher level of physical fitness than students with a BMI in the underweight, overweight, or obese categories. This study contributes to the development of more effective health intervention programs, especially in the context of the student community, to support the creation of a holistic healthy lifestyle.